Is There a Diminishing Value of Urban Amenities as a Result of the COVID-19 Pandemic? - Aico van Vuuren (Institute of Labor Economics (IZA), 2022)
We investigate whether the COVID-19 pandemic decreased the willingness to pay for urban amenities such as restaurants, cinemas and theaters. We do this by using a hedonic pricing model in combination with a time-gradient difference-in-difference approach. We use a data set that contains virtually all apartments for sale in the larger Stockholm area. We use a very detailed and flexible definition of density of urban amenities based on the exact location of these amenities and the walking distance from the apartments to these amenities. We find a decrease of 1.9 percent of apartments that we label as amenity rich.
Keywords: R00; R23; R30; 330; COVID-19; urban economics; amenities